The phenomenological body of Merleau -ponty's space of meaning - Farha, Mohammad; Mallah, Heba (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research tries to show the importance of the body as a body awares the world, and to consider this body as an open unite of expression and speech, then the research attempts to show the characteristic the relationship between signifier and signified in the field of linguistic expression. which is related to intentional words and spoken or written signs which the self-body tends to them, Moreover the research explains Merleau- ponty's interest what he calls indirect language which is aesthetic arts, and studying the feasibility of attracting the art of drawing and dancing to philosophy of silent language. The body is the possibility of my being which has bodily and linguistic gestures, it is a special nature in which the body interacts with its movement. Exploring the bodily Cogito between silence and speech, and their role in the producing of meaning in the body between visible and non- visible.